International economic relations of the Western world, 1959-1971 : v.1, Politics and trade - Oliver, Hermin; Shonfield, Andrew (New York : Oxford University Press, 1976)
Contents. v.1 Politics and trade. v.2 International monetary relations.
Keywords: International economic relations